The Implementation of Religious Moderation in Pesantren Bayt Al-Qur'an, South Tangerang: A Living Qur'an Study - Abbas, Ahmad Jauhari; Prasetya, Vania Anasya Dewi; Rizkon, Muhammad; Huda, Ade Naelul (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2024)
This study aims to examine and explore the implementation of religious moderation in Pesantren Bayt Al-Quran South Tangerang. Pesantren plays a significant role in maintaining the integrity of the Unitary State of the Republic of Indonesia, a country with a diverse population, including in terms of ethnicity, culture and religion. Additionally, the pesantren community is heterogeneous in which on a small scale, the attitude and daily life of the pesantren community reflect Indonesia's diversity. Qualitative research methods were employed using field research and a living Qur'an approach. The data were obtained through direct interviews, questionnaires via Google form and observation, and then analysed by using descriptive analysis. The indicators used were initiated by the Ministry of Religious Affairs of the Republic of Indonesia, namely national commitment, tolerance, non-violence and adaptability to local culture. The findings indicated that Pesantren Bayt Al-Qur'an South Tangerang has implemented religious moderation in its daily life and in various aspects of life. The most evident indicator of religious moderation is tolerance.